2021
DOI: 10.3390/nu13031013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gut Microbiome in Korean Patients with Metabolic Associated Fatty Liver Disease

Abstract: Metabolic associated fatty liver disease (MAFLD) is a new concept where the presence of both fatty liver and metabolic abnormality are necessary for diagnosis. Several studies have reported that altered gut microbiome is closely associated with metabolic diseases and non-alcoholic fatty liver disease. However, the studies on MAFLD population are scarce. This prospective study aimed to identify differences in gut microbiome between patients with MAFLD and healthy controls in Korean population. In this study, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 45 publications
4
27
0
Order By: Relevance
“…Significant associations of this taxon with these diseases have been identified, but both greater and lesser abundance have been reported [43] , [45] , [46] , [47] . Megamonas and Ruminococcus have been previously shown to be associated with severe NAFLD (NASH or significant fibrosis) [7] , [8] , [48] , [49] , and we found that it was only significantly less abundant in patients with fibrosis but no T2D.…”
Section: Discussionsupporting
confidence: 51%
“…Significant associations of this taxon with these diseases have been identified, but both greater and lesser abundance have been reported [43] , [45] , [46] , [47] . Megamonas and Ruminococcus have been previously shown to be associated with severe NAFLD (NASH or significant fibrosis) [7] , [8] , [48] , [49] , and we found that it was only significantly less abundant in patients with fibrosis but no T2D.…”
Section: Discussionsupporting
confidence: 51%
“…MAFLD patients also showed decreased counts of butyrate-producing bacteria and increased counts of ethanol-producing bacteria. 118 A decreased abundance in Faecalibacterium has been also reported in another large survey in 1148 adults, 205 of whom having NAFLD. 119 A prospective study in a cohort of 766 subjects showed a lower richness in gut microbiota, high abundance of Fusobacteria and low abundance of genera Oscillospira and Ruminococcus of the family Ruminococcaceae and genus Coprococcus of the family Lachnospiraceae in subjects with persistent NAFLD, as compared controls 112 Thus, the strongest evidence should point towards a lower abundance of Bacteroidetes and Firmicutes, and to an increased abundance of Lactobacillaceae in NAFLD patients, as compared with healthy controls.…”
Section: Microbiota In Nafld Patientssupporting
confidence: 58%
“…A prospective study in Korean subjects revealed increased phylum Proteobacteria , family Enterobactereriaceae , genus Citrobacter abundance, and decreased genus Faecalibacterium in the presence of MAFLD, compared to controls. MAFLD patients also showed decreased counts of butyrate‐producing bacteria and increased counts of ethanol‐producing bacteria 118 …”
Section: Characterization Of Gut Microbiota In Nafld Patientsmentioning
confidence: 99%
“…Recent evidence has confirmed the crucial contribution of gut microbial dysbiosis to NAFLD pathogenesis, scrutinizing the importance of homeostasis in the gut–liver axis. Shotgun sequencing results from feces of metabolic-associated NAFLD patients displayed an elevated abundance of ethanol-producing bacteria and a decreased abundance of butyrate-producing bacteria [ 91 , 92 ]. In obese NAFLD patients, steatosis was positively correlated with dysregulation of the microbial BCAA metabolism, in which its biosynthesis is upregulated [ 15 ].…”
Section: Bcaa Promotes Hepatic Health Through Modulation Of Gut Micro...mentioning
confidence: 99%